Garlic consumption and colorectal cancer risk in US adults: a large prospective cohort study - Jiang, Zongze; Chen, Huilin; Li, Ming; Wang, Wei; Long, Feiwu; Fan, Chuanwen (Frontiers in Nutrition, 2023)
Objective: To clarify the inconsistent findings of epidemiological studies on the association between dietary garlic consumption and colorectal cancer (CRC) incidence, by prospectively assessing the association in a large US population.Methods: Data of 58508 participants (aged 55-74) from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial were analyzed. Dietary data were collected using a validated questionnaire. Multivariable Cox regression analysis determined hazard ratio (HR) and 95% confidence interval (CI). Restricted cubic spline regression was used to investigate the non-linear relationship, and subgroup analysis was conducted to examine potential effect modifiers.Results: During a median follow-up of 12.05 years, 782 CRC cases were documented, including 456 proximal colon cancer cases, 322 distal CRC cases, and 4 CRC cases with an unknown site.Moderate dietary garlic consumption was significantly associated with a reduced risk of overall CRC (HR quintile 3 vs. 1: 0.70, 95%CI: 0.54 to 0.91, p=0.007, P for trend: 0.434), exhibiting a Ushaped dose-response pattern, and also with overall CRC in males in the stratified Cox regression model (Model 2: HR quintile 3 vs. 1: 0.57, 95%CI: 0.40 to 0.81, p=0.002), but not in females. The protective association was more pronounced in men, Caucasian, and those with lower alcohol consumption. Notably, these protective effects were observed for overall distal CRC (HR quintile 3 vs. 1: 0.62, 95%CI: 0.42 to 0.93, p=0.021; and HR quintile 4 vs. 1: 0.63, 95%CI: 0.43 to 0.92, p=0.018, P for trend: 0.208); and for distal CRC in males (HR quintile 3 vs. 1: 0.40, 95%CI: 0.22 to 0.71, p=0.002, P for trend: 0.696), but not for proximal CRC.Conclusions: Moderate consumption of dietary garlic is associated with a decreased CRC risk in the US population, with variations based on CRC anatomic subsites. Further in-depth prospective studies are needed to validate these findings in different populations and to explore subsites-specific associations.